2018
DOI: 10.1111/gcb.14160
|View full text |Cite
|
Sign up to set email alerts
|

Phenological sensitivity to climate change is higher in resident than in migrant bird populations among European cavity breeders

Abstract: Many organisms adjust their reproductive phenology in response to climate change, but phenological sensitivity to temperature may vary between species. For example, resident and migratory birds have vastly different annual cycles, which can cause differential temperature sensitivity at the breeding grounds, and may affect competitive dynamics. Currently, however, adjustment to climate change in resident and migratory birds have been studied separately or at relatively small geographical scales with varying tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 56 publications
(104 reference statements)
3
85
0
Order By: Relevance
“…synchrony of phenology, antipredator defences, competitive interactions). For example, because the migrant pied and collared flycatchers display shallower reaction norms to temperature than blue tits, they breed later in warmer environments, and suffer from competition with resident tit species [92]. An important step would be to increase The open circles represent the mean phenology (mean laying date or mean caterpillar peak date).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…synchrony of phenology, antipredator defences, competitive interactions). For example, because the migrant pied and collared flycatchers display shallower reaction norms to temperature than blue tits, they breed later in warmer environments, and suffer from competition with resident tit species [92]. An important step would be to increase The open circles represent the mean phenology (mean laying date or mean caterpillar peak date).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In general, warmer conditions at the start of a breeding season favor earlier egg‐laying initiation dates (Dunn , Visser and Both , Visser et al , Ockendon et al , Phillimore et al ). The long‐term trend toward earlier egg laying by species exposed to increasing spring temperatures due to climate change has also been widely documented (Matthysen et al , Charmantier and Gienapp , Dunn and Møller , Phillimore et al , Källander et al , Samplonius et al ).…”
Section: Discussionmentioning
confidence: 90%
“…These results are interesting in the light of ongoing climate change, which differentially alters the phenology and distribution of interspecific competitors (Carter et al, ; Phillimore et al, ; Samplonius et al, ; Usui et al, ). It is generally shown that resident species are more plastic in their response to temperature than migrants (Phillimore et al, ; Samplonius et al, ), causing their breeding phenologies to diverge. Such differential divergence has been shown to affect information use (Samplonius & Both, ), and here I show it could affect competitive interactions.…”
Section: Discussionmentioning
confidence: 92%
“…Such differential divergence has been shown to affect information use (Samplonius & Both, ), and here I show it could affect competitive interactions. This could mean that arriving competitors will encounter fewer aggressive great tits as climate change continues, because great tits advance their breeding phenology more than later breeding migrants in response to temperature (Samplonius et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation